Dose-Intensity of Bisphosphonates and the Risk of Osteonecrosis of the Jaw in Osteoporosis Patients - Jung, Sung-mok; Han, Sujeong; Kwon, Hye-Young (Frontiers in Pharmacology, 2018)
Objective: To examine the incidence rates and association between dose-intensity, stratified by exposure duration, of bisphosphonates and the risk of osteonecrosis of the jaw among Korean osteoporotic patients older than 50 years. Study Design and Setting: Using the population-based National Health Insurance Claims Data of Korea from January 1, 2006, through December 3, 2012, 13,730 new bisphosphonate users as of 2006 were identified. Truncated age-standardized incidence rate estimation and multivariate logistic regression analyses were conducted. Results: In this retrospective cohort study, increasing age-standardized incidence rates of ONJ attributed to bisphosphonate exposure were observed for individuals with less than 1 year, 1~2 years, over 2 years of defined daily dose (DDDs) of bisphosphonate exposure (13.85, 16.19, and 38.20, respectively), using a truncated 2000 U.S. Standard Population. Also, over 2 years of bisphosphonate DDDs was associated with an increased risk of developing of ONJ with an adjusted odds ratio of 1.51 (95% confidence interval: 1.31–1.75), compared to individuals with less than 1 year of bisphosphonate exposure. Conclusion: Our data provided the evidence to support the association between risk of ONJ and duration of bisphosphonate exposure used in the treatment or prevention of osteoporosis.